Variations in the Indonesian sauromatum horsfieldii Miq. (Araceae) based on characteristics of morphology, anatomy and cytology - Yuzammi; Astuti, Inggit Puji; Handayani, Tri; Yulistyarini, Titut; Hadiah, Julisasi Tri (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sauromatum horfieldii Miq. (Araceae) is distributed from India, China to South East Asia. In Indonesia, the species only occurs in Sumatera, Jawa, and Bali. This study investigated the morphological, anatomical, and cytological diversity of three populations of the species, one from each of these Indonesian islands. The results showed that there was variation in morphology of the petiole, number of leaflets and leaf margin. The stomatal complex consisted of elliptical pores with reniform guard cells and two or three subsidiary cells. The Indonesian plants of S. horsfieldii possessed two stomatal types, namely anomocytic and anisocytic, both with abaxial distribution (hypostomatic). Measurements on each population showed average stomatal indices (SI) of 10.01, 10.02 and 14.55, average stomatal lengths of 34.6, 33.8 and 29.50 μm, and average stomatal widths of 20.8, 21.1 and 16.50 μm for Sumatera, Jawa, and Bali, respectively. The epidermal cells are mostly irregular and somewhat undulate. The chromosome number for all the accessions was 2n = 26.